2017
DOI: 10.1007/s11356-017-9514-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-duration hydrothermal fermentation of food waste: preparation of soil conditioner for amending organic-matter-impoverished arable soils

Abstract: Soil conditioners can be used to compensate for the insufficient soil nutrition and organic matter (OM) of arable soils. However, the traditional preparation method for soil conditioners is lengthy and requires facilities that occupy large tracts of land. In this study, a short-duration hydrothermal fermentation (SHF) method was developed for the preparation of soil conditioners from food waste. The SHF method required only 18 h to produce soil conditioners with physicochemical characteristics that were simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Aerobic composting is a relatively environmentally friend technology for food waste treatment, as foods contain high concentrations of easily degradable organic substances and nutrients which are easily to be decomposed ( Hou et al, 2017 ). Studies have found that food waste composted with Chinese medicinal herbal residues ( Zhou, Selvam & Wong, 2018 ), green waste ( Williams et al, 2019 ), sugarcane leaves ( Shan et al, 2019 ), cattle manure ( Xing et al, 2019 ), pig manure ( Dennehy et al, 2017 ; Jiang et al, 2018 ), chicken manure ( Saad, Rahman & Yusoff, 2019 ) could be processed to form biological fertilizers, which would increase organic matters in the soil and improve the soil structure ( Wang & Zeng, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerobic composting is a relatively environmentally friend technology for food waste treatment, as foods contain high concentrations of easily degradable organic substances and nutrients which are easily to be decomposed ( Hou et al, 2017 ). Studies have found that food waste composted with Chinese medicinal herbal residues ( Zhou, Selvam & Wong, 2018 ), green waste ( Williams et al, 2019 ), sugarcane leaves ( Shan et al, 2019 ), cattle manure ( Xing et al, 2019 ), pig manure ( Dennehy et al, 2017 ; Jiang et al, 2018 ), chicken manure ( Saad, Rahman & Yusoff, 2019 ) could be processed to form biological fertilizers, which would increase organic matters in the soil and improve the soil structure ( Wang & Zeng, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this article did not consider them as organic fertilizers. During fermentation process, various components in food waste are converted into stable humus-like substances and rapidly available nutrients, which can be quickly hydrolyzed ( Bi et al, 2019 ), or directly absorbed by plants ( Hou et al, 2017 ). Those materials could also improve nutrition levels of the soil ( Du et al, 2018 ) and could be generally beneficial to soil microbial communities ( Liu et al, 2020 ) which are closely related to soil fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic composting is currently a relatively environmentally friend technology for food waste treatment, as it contains high concentrations of easily degradable organic substances and nutrients which are easily to be decomposed (Hou et al 2017 (Saad et al 2019) to form biological fertilizer, could increase organic matters in the soil and improve the soil structure (Wang and Zeng 2018). Therefore, the degradable food waste, especially rural food waste could be used on-site as fertilizers for organic crop production, reducing transportation costs and increasing farmers' income.…”
Section: Nitrogen Reservoir Of Biodegradable Household Garbage In Different Componentsmentioning
confidence: 99%
“…Therefore, this article did not consider treating them as organic fertilizers. During fermentation process, various components in food waste are converted into stable humus-like substances and rapidly available nutrients, which can be quickly hydrolyzed (Bi et al 2019), or directly absorbed by plants (Hou et al 2017). Those materials could also improve nutrition levels of the soils (Du et al 2018).…”
Section: Potential Of Biodegradable Household Garbage Of Replacing Chemical Fertilizersmentioning
confidence: 99%
“…For instance, it is suitable to be processed into a stable and nutrient-rich biological fertilizer (Haddad and Batarseh 2019;Waqas et al 2019). Studies have demonstrated that food waste could be fermented to prepare soil conditioners, which might decrease carbon emission and improve land use e ciency (Hou et al 2017). Some found that long-term application of food waste could increase total organic carbon content in orchard soils and improve soil fertility (Jia et al 2019).…”
Section: Introductionmentioning
confidence: 99%